Environmentally friendly fire-resistant epoxy resins based on a new oligophosphonate with high flame retardant efficiency. Issue 27 (26th February 2016) - Hamciuc, Corneliu; Vlad-Bubulac, Tachita; Serbezeanu, Diana; Carja, Ionela-Daniela; Hamciuc, Elena; Lisa, Gabriela; Pérez, Vicente Forrat
Abstract : New fire resistant epoxy resins were prepared. The kinetic processing of thermogravimetric data was performed using Friedman and Vyazovkin methods. Abstract : Advanced flame retardant epoxy resins, environmentally friendly, with different contents of a new oligophosphonate (PFR ), were prepared using dicyandiamide as a hardener and 1, 1-dimethyl-3-phenylurea as an accelerator.PFR, with a high phosphorus content, was synthesized by polycondensation reaction of phenylphosphonic dichloride with a phosphorus-containing bisphenol, namely bis((6-oxido-6 H -dibenz[ c, e ][1, 2]oxaphosphorinyl)-(4-hydroxyaniline)methylene)-1, 4-phenylene. The bisphenol was prepared by reacting 9, 10-dihydro-oxa-10-phosphaphenanthrene-10-oxide with an imine bisphenol resulting from the condensation of 4-aminophenol with terephthalaldehyde. The structure and morphology of cured epoxy resins were evaluated by Fourier transform infrared spectroscopy and scanning electron microscopy (SEM) analysis, respectively. Differential scanning calorimetry analysis revealed that cured epoxy resins containingPFR possessed slightly higher glass transition temperatures than phosphorus-free cured epoxy resin. Thermogravimetric analysis and limiting oxygen index values indicated that the incorporation ofPFR into epoxy resin substantially enhanced the thermal stability and flame retardancy of the char layer at high temperature. The surface morphology of the char residue was studied by SEM measurements. The kinetic processing of thermogravimetric data was carried out using Friedman and Vyazovkin methods. The lifetime prediction analysis established that the fire-resistant phosphorus-containing epoxy resins could be used at a constant temperature of 200 °C up to 620–630 minutes. The newPFR can be successfully used as a very efficient flame retardant for improving the fire-resistance properties of epoxy resins.